Peninggalan Kolonial di Kampung Makian - Marlyn Salhuteru (Kapata Arkeologi, 2007)
Mace Producer or recognized with term spice island, Moluccas become Europe nations capture. Initially Portugis, later; then Spanyol and Dutch. Occupying Footstep nation Europe can be traced [by] through archaeological ommission [is] which leaving of. Moluccas represent very rich region with colonial epoch ommission. This article try to lift somes archaeology ommissiion from a period of to colonial which is there are Kampung Makian, one of countrified in Bacan, South Halmahera. Archaeological data in Kampung Makian show the regional role at a period of colonial.